INCLUSIVE LANGUAGE EDUCATION: POLICY AND MANAGEMENT FOR LEARNERS WITH SPECIAL NEEDS - Ergasheva Ozodabonu Bahodirjon qizi (NEW SCIENTIFIC PERSPECTIVES AT THE INTERSECTION OF LANGUAGE, CULTURE, AND TECHNOLOGY, 2025)
Abstract: Inclusive language education is critical in ensuring equitable learning opportunities for all students, particularly those with special needs. This study investigates how effective educational policies and management practices can foster inclusive language learning environments. Through an analysis of current frameworks, case studies, and international models, the paper identifies key strategies to implement inclusive education, including teacher training, curriculum adaptation, and collaborative policy development. The findings emphasize that sustainable inclusion requires systemic policy reform and a commitment to learner-centered education.